Ali beremo maturitetne romane z užitkom ? - Zupan Sosič, Alojzija (Jezik in slovstvo, 2003)
Reading Alamut, a novel studies for secundary school final examinations (matura) can be pleasureable, if the teacher - in guiding analytical and creative reading - changes roles from that of monitor to guide for student reading, while at the same time helping the students to become aware of the multi-layered structure of the novel. In the paper, I suggest several possibilities for introducing the novel in a historical, philosophical and religious, and psychological perspectives, by presenting the novel as a sketch for relaxing and effective literary reading.
Keywords: Bartol, Vladimir, 1903-1967; Slovene literature; slovenska književnost; književnost; literature; didactic method; didaktika; matura; novel; roman; branje; Bartol, Vladimir: Alamut